Annual Report 2023: Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) - Accelerating Impacts of CGIAR Climate Research for Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) is a project administered by the Alliance of Bioversity International and the International Centre for Tropical Agriculture (CIAT). Activities financed by the World Bank’s International Development Association (IDA) through AICCRA are undertaken by a broad coalition of partners working at continental, regional, and national levels. In 2023, AICCRA reached more than four million individuals in Africa with the tools, technologies, and practices that promote climate-smart agriculture. 1.7 million of them were women. The achievements of AICCRA this year demonstrate a collaborative spirit and the dedication of its team in delivering compelling outcomes with partners and stakeholders. Together, we have exceeded all the Project Development Objectives (PDOs) for 2023, surpassing the overall targets set at the beginning of the year. This success reflects a collective effort and the strong partnerships built with CGIAR research centers in Africa, African national and regional organizations, and diverse stakeholders and beneficiaries – most importantly, smallholder farmers.